Media Pembelajaran Sejarah di SMK Negeri Pontianak - Astrini Eka Putri; Sariyatun; Nunuk Suryani (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
Research is expected could become the foundation of renewal in the use of media teaching history in state vocational schools in Pontianak. Based on it, then the researcher wants to describe about media learning customarily using by teachers in the process teaching history. Researcher interested to arrange research with a title “Media Teaching History in State Vocational Schools in Pontianak“. Media uses teaching history in state vocational schools Pontianak has been good enough, since on average teachers using the existing facilities at the school in order to support learning activity. Learning activity history done by the teacher in this has been good enough, because it is already employing variations learning that are attractive. In the teaching process in two classes not only uses the media learning of a textbook, but had done some innovation that is by using media Microsoft Office PowerPoint.